Topological Entropy of One Type of Nonoriented Lorenz-Type Maps - Guo Feng (Discrete Dynamics in Nature and Society)
Constructing a Poincaré map is a method that is often used to study high-dimensional dynamical systems. In this paper, a geometric model of nonoriented Lorenz-type attractor is studied using this method, and its dynamical property is described. The topological entropy of one-dimensional nonoriented Lorenz-type maps is also computed in terms of their kneading sequences.